The Ugaritic Verbal System. Ph. D. - Fenton, Terry Leonard (2015)
Typewritten; G. R. Driver; Use of qtl- and yqtl-forms reflects two periods; in the second qtl replaces уqtl as the narrative “tense”. The findings confirm M. Liverani’s conclusions.